Problem Based Learning Learning Model for Improving The Mathematical Problem Solving Ability of Grade VIII Students of SMPN 1 Damar - Murnaka, Nerru Pranuta; Satria, Satria; Haryanti, Haryanti; Indira, Elizabeth Wahyu Margareth (Universitas Wiralodra, 2023)
Problem-solving ability is one of the higher-order thinking skills (HOTs) that students need in facing the 21st century. The reality on the ground shows that students' problem-solving abilities are still below the KKM. In efforts to overcome this problem, researchers apply Problem Based Learning (PBL) learning to improve students' problem-solving abilities. The research conducted aims to investigate whether the magnitude of the increase in the problem-solving ability of students who learn using the PBL model is higher than that of students who learn using conventional learning. This research is a quantitative study with a non-equivalent pretest-posttest control group design. The population in this study were all students of class VIII SMP Negeri 1 Damar, East Belitung Regency, while the research sample was class VIIIA class VIIIB. The research sample was selected by a simple random sampling technique. The instrument used in this study was a test. The results of the data analysis show that the magnitude of the increase in the mathematical problem-solving ability of students who learn using the PBL model is higher than that of students who learn using conventional learning